Cybergossip and Problematic Internet Use in cyberaggression and cybervictimisation among adolescents - Cebollero-Salinas, Ana; Orejudo, Santos; Cano-Escoriaza, Jacobo; Íñiguez-Berrozpe, Tatiana (Computers in human behavior, 2022)
Research on cyberbullying has focused on personal and contextual factors. However, little is known about its relationship with habitual behaviours associated with easy access to the Internet, such as cybergossip and problematic Internet use, as well as the role that gender and age play in relation with these variables. Knowledge about these subjects could contribute to the elaboration of new preventive and educational approaches. This study therefore aims to analyse the influence that cybergossip and problematic Internet use have on cyberaggression and cybervictimisation, considering differences in age, gender, and the age at which the first smartphone was owned. 1013 adolescents between 12 and 18 years old (M = 14.0, SD = 1.42) (56.4% girls) from thirteen Spanish educational centres participated. The results, obtained through structural equation modelling, show that there is a high association between the four constructs, and explain a high variability of cyberaggression and cybervictimisation. It is relevant that cybergossip has a greater influence on the cyberaggression of girls, on subjects who are 12–14 years old, and on victims aged 15–18, while problematic Internet use has a greater influence on the cybervictimisation of boys and subjects who are 12–14 years old. Furthermore, the fact of having had a smartphone before the age of 11 leads to a higher level of cyberaggression, explained by cybergossip and problematic Internet use. These results allow us to establish new channels of intervention. •Cyberbullying is associated with problematic Internet use (PIU) and cybergossip.•Cybergossip explains significantly cyberaggression of girls and 12–14 subjects.•Cybervictimization from age 15 on is explained to a greater extent by cybergossip.•PIU has a greater influence on the cybervictimisation of boys and 12–14 subjects.•For cyberaggression, it is relevant to have had a smartphone before the age of 11.